2016
DOI: 10.1007/s12160-016-9793-9
|View full text |Cite
|
Sign up to set email alerts
|

Health Communication in Social Media: Message Features Predicting User Engagement on Diabetes-Related Facebook Pages

Abstract: These findings hold promise for guiding communication design in health-related social media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
82
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 23 publications
11
82
2
1
Order By: Relevance
“…Facebook posts with images have been found to elicit more engagement than posts without images. 20 With interactive posts, the user's input would be re- Importantly, this study showed that there was a lack of information for the layperson interested in finding educational material about dental trauma on Facebook. Only 14 posts (4.3%) included information on risk factors and prevention of dental trauma.…”
Section: Discussionmentioning
confidence: 92%
“…Facebook posts with images have been found to elicit more engagement than posts without images. 20 With interactive posts, the user's input would be re- Importantly, this study showed that there was a lack of information for the layperson interested in finding educational material about dental trauma on Facebook. Only 14 posts (4.3%) included information on risk factors and prevention of dental trauma.…”
Section: Discussionmentioning
confidence: 92%
“…37 Research consistently has found that posting photos results in a greater amount of engagement than other post types. 31,38,39 A study of scientific communication with the public across social media platforms by the European Organization for Nuclear Research found that “wow” photographs (i.e., awe-inspiring photographs) produced the most engagement, especially when posted on the photo-emphasizing platform Instagram. 40 Another recurring finding is that users may prefer different social media platforms, making formative research and/or use of multiple channels an important consideration.…”
Section: Key Principles Of Social Media To Enhance Cancer Prevention mentioning
confidence: 99%
“…Research has shown that women respond more favorably to preventative health care and associated research when they believe their participation or action will be of some benefit to their family or friends (Newington et al, 2014). Tone and imagery may modify this effect (Rus & Cameron, 2016).…”
Section: Aim 3 Introductionmentioning
confidence: 99%